Chaetomitrium Pseudoelongatum - Monica Suleiman; Hiroyuki Akiyama (2014)
(1) Plants are densely tufted, (2) branches are sub-erect; (3) branch leaves slightly flattened, erect-patent, deeply concave, rugose above, widely obtuse or almost truncate with minute apiculus; (3) leaf margins are incurved above, forming constriction below apices, serrate above, denticulate below with simple teeth; (4) costae are strong; (5) lamina cells are thick-walled, smooth, and shorter at apex; (6) setae are 8-9 mm long, papillose half above but smooth below; (7) capsules inclined, pustulose below, and apophysis strongly rugose: (8) calyptrae hispid above, with long cilia at the base.